2020
DOI: 10.1097/mnm.0000000000001136
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of PD-L1 expression on tumor cell and tumor infiltrating immune cell with 18F-fluorodeoxyglucose uptake on PET/computed tomography in surgically resected pulmonary adenocarcinoma

Abstract: Objective The uptake of 18F-fluorodeoxyglucose (18F-FDG) PET/computed tomography (CT) is known to be linked to programmed death ligand 1 (PD-L1) expression on tumor cells (TC). However, the association between PD-L1 expression on immune cells (IC) and 18F-FDG accumulation is still unclear. Here, we conducted a clinicopathological study to investigate the relationship between PD-L1 expression on TC/IC and 18F-FDG uptake in patients with surgically resected pulmonary adenocarcinoma (ADC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The remaining seven full text articles were assessed for eligibility and one article was excluded due to insufficient data for the calculation of sensitivity and specificity of 18F‐FDG PET or PET/CT for the prediction of PD‐L1 expression in NSCLC patients. Finally, six studies were selected that were eligible for systematic review and meta‐analysis and no additional studies were found screening the references of these articles 22–27 . The characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining seven full text articles were assessed for eligibility and one article was excluded due to insufficient data for the calculation of sensitivity and specificity of 18F‐FDG PET or PET/CT for the prediction of PD‐L1 expression in NSCLC patients. Finally, six studies were selected that were eligible for systematic review and meta‐analysis and no additional studies were found screening the references of these articles 22–27 . The characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Also, studies included in this meta‐analysis used different definition for positivity of PD‐L1 protein expression. Four studies used the cutoff value of 5% for defining PD‐L1 positivity 23–25, 27 and another two studies used 1% for positivity 22, 26 . Immunohistochemical analysis were performed using different methods to determine PD‐L1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations